2017
DOI: 10.1074/jbc.m117.785022
|View full text |Cite
|
Sign up to set email alerts
|

Lysine desuccinylase SIRT5 binds to cardiolipin and regulates the electron transport chain

Abstract: Edited by George M. Carman SIRT5 is a lysine desuccinylase known to regulate mitochondrial fatty acid oxidation and the urea cycle. Here, SIRT5 was observed to bind to cardiolipin via an amphipathic helix on its N terminus. In vitro, succinyl-CoA was used to succinylate liver mitochondrial membrane proteins. SIRT5 largely reversed the succinyl-CoA-driven lysine succinylation. Quantitative mass spectrometry of SIRT5-treated membrane proteins pointed to the electron transport chain, particularly Complex I, as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 32 publications
7
69
0
Order By: Relevance
“…7B), suggesting that complex formation is normal. This is consistent with previously published findings in SIRT5KO livers (10).…”
Section: Sirt5 Is Required For Survival Post-tacsupporting
confidence: 94%
See 2 more Smart Citations
“…7B), suggesting that complex formation is normal. This is consistent with previously published findings in SIRT5KO livers (10).…”
Section: Sirt5 Is Required For Survival Post-tacsupporting
confidence: 94%
“…7D). Supporting this model, SIRT5 was recently described to regulate oxidative phosphorylation via its desuccinylase activity in liver (10), which identified the electron transport chain as the top pathway targeted by SIRT5 and further found that complex II and ATP synthase activities were significantly decreased in mitochondria isolated from SIRT5KO mouse liver.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Coordinated function of SIRT3 and SIRT5 in the regulation of ureagenesis agrees well with the regulation of both sirtuin genes by PGC-1α, a fasting-activated transcriptional regulator (2). SIRT5 targets several components of the electron transport chain (140). It was first originally reported that SIRT5 has a suppressive effect on cellular respiration (91).…”
Section: Sirt5 the Regulator Of The Urea Cycle And What Else?supporting
confidence: 65%
“…It was first originally reported that SIRT5 has a suppressive effect on cellular respiration (91). However, several more recent studies have observed positive effects on oxidative phosphorylation (12,140,143).…”
Section: Sirt5 the Regulator Of The Urea Cycle And What Else?mentioning
confidence: 99%